Theorizing Digital Religiosity: Post-Secular Islam, Platform Dynamics, and the Quba-Dirar Framework - Arifin, Syamsul; Tung, Le Xuan; Wijaya, Rahmad; Zuhri, Achmad Muhibbin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2026)
The secularization thesis is increasingly inadequate for explaining Islam’s expanding presence within Indonesia’s digital public sphere. This article addresses a critical limitation in contemporary digital Islam scholarship: while existing approaches effectively describe how religion operates across digital environments, they provide limited conceptual resources for evaluating whether such engagements advance or compromise Islam’s ethical and normative purposes. Drawing on post-secular theory, platform studies, and the normative-historical perspectives of Fazlur Rahman and M. Amin Abdullah, this study develops the Quba-Dirar heuristic, an evaluative framework derived from a Quranic historical paradigm. The framework distinguishes between forms of digital religiosity that cultivate ethical piety and social cohesion (Digital Quba) and those that instrumentalize religious symbols for polarization, political mobilization, or commercial gain (Digital Dirar). Applied to the Indonesian context, the analysis yields three principal findings. First, digital platformization has intensified the deprivatization of Islam within the public sphere. Second, algorithmic architectures have facilitated new configurations of religious authority through micro-celebrity actors operating beyond established scholarly institutions. Third, these transformations generate structural pressures toward Digital Dirar irrespective of individual institutions. The article argues for an integrative epistemology in Islamic studies that simultaneously combines empirical analysis and normative evaluation within a single analytical framework.